PROBING FTD GENETICS WITH NEXT-GENERATION SEQUENCING. Issue 12 (15th November 2016) - Koriath, Carolin; Adamson, Gary; Druyeh, Ron; Kenny, Janna; Rossor, Martin; Schott, Jon; Collinge, John; Fox, Nick; Rohrer, Jon; Mead, Simon
Abstract : In a previous study of the UCL frontotemporal dementia (FTD) cohort, 40% of patients reported some family history of dementia but only 20% carried a mutation in GRN or MAPT. Since then, other genes have been shown to cause FTD and more widespread next-generation sequencing (NGS) offers the potential to simultaneously screen for all known causal genes. We applied a validated 17-gene NGS dementia panel combined with PCR-based assessments of the C9orf72 and PRNP expansions to the UCL FTD DNA cohort (n=381). We classified mutations by likelihood of pathogenicity and compared with demographic and clinical data. 39% of patients report some family history but only 13% had an autosomal-dominant history. 27.6% of patients carried a deleterious variant; a further 6.0% had potentially deleterious variants. Most deleterious mutations were found in C9orf72, GRN or MAPT, while other genes amounted to 6.8%. Only 26.9% of patients with a strong family history did not have a deleterious mutation. Custom panel provide affordable high-quality sequencing. With additional C9orf72 testing, they can assess the most FTD genes and mutations in more unusual genes occur at a significant rate. NGS identifies an abundance of novel or uncertain variants; these will require considerable work to classify correctly.